Analisis Faktor-Faktor Penyebab Kecelakaan Lalu Lintas Ruas Jalan Mawasangka Tengah-Mawasangka Kabupaten Buton Tengah - Muh Said Waristo; Al Tafakur La Ode; Ghefra Rizkan Gaffara; Septi Adnan; Fadila Fadila (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
The aim of this study was to analyze the factors causing traffic accidents along the Mawasangka Tengah-Mawasangka road section in Central Buton Regency. Traffic accidents are influenced by various interrelated factors, which can generally be classified into two main categories: human factors and technical factors. Technical factors include road infrastructure conditions, traffic flow characteristics, and pavement conditions. Based on the accident analysis conducted in the study area, it was found that accidents were predominantly caused by driver error or negligence rather than by other contributing factors. The accident data were obtained from the Central Buton Police Department and supported by direct field surveys conducted at identified blackspot locations along the Mawasangka Tengah-Mawasangka road section. The analysis employed the Cumulative Sum (CUSUM) method and the Accident Equivalent Number (AEK) method to identify accident-prone locations and assess accident severity. The results indicate that: (1) the primary blackspot location along the Mawasangka Tengah-Mawasangka road section is situated in Mawasangka Tengah District, accounting for 53.93% of the total recorded traffic accidents, with 48 accident cases recorded during the study period and an AEK value of 255, indicating a high level of accident severity; and (2) the contributing factors to traffic accidents were dominated by human factors (67.42%), followed by road conditions (16.85%), physical environmental conditions (13.48%), and vehicle factors (6.74%). Therefore, it can be concluded that human factors are the dominant cause of traffic accidents on the Mawasangka Tengah–Mawasangka road section, contributing 67.42% of all recorded accident cases.